Discrimination, criminalization and xenophobia in the media: The case of Venezuelan migration in Brazil, Colombia, Ecuador, and Peru - Aguilar, Sergio Luiz Cruz [UNESP] (Taylor & Francis, 2024)
In South America, Venezuela’s political, economic, and social crisis resulted in mass migration towards countries such as Brazil, Colombia, Ecuador, and Peru. This migratory movement provoked negative media narratives associating Venezuelan migrants with security concerns. This chapter examines how Brazilian, Colombian, Ecuadorian, and Peruvian newspapers have portrayed Venezuela’s mass migration between 2015 and 2021. I argue that the use of negative language surrounding immigrants is more common in some countries than others, and that would be a nexus between negative discourse, the number of migrants, and the social, economic, and political conditions of the host country as well as restrictive measures targeting migrants. After examining the specific newspapers in the four countries, this study concludes that in Brazil and Colombia, there was no perceived relationship between the arrival of migrants, economic growth variation, and negative news or restrictive measures. In turn, in Ecuador and Peru, there was a potential correlation between the arrival of Venezuelan migrants, economic variation in the country, an increase in the negative news pieces of the newspapers investigated and restrictive measures adopted by governments.